Perceived Facilitators and Barriers, From the Perspective of Users, of a Multicomponent Intervention in Older People Using an Asynchronous Telehealth Modality During the COVID-19 Pandemic: A Qualitative Research - Rafael Pizarro-Mena; Samuel Duran-Aguero; Maria Causa-Vera; Camilo Rios-Duran; Solange Parra-Soto (Journal of Aging Research)
Conclusion: This is the first qualitative study that identifies facilitators and barriers of a multicomponent intervention in an asynchronous telehealth modality, as a continuation of the same face-to-face intervention. The asynchronous telehealth modality could be used regularly with older people in rural areas, in situations of disability and/or with care needs, pandemic scenarios, or natural disasters.